Enhancing preservice teacher education: Integrating assistive technology and UDL within the TPACK framework: A systematic literature review - Wang, Shizhao; Sitthiworachart, Jirarat (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the integration of assistive technology (AT) and Universal Design for Learning (UDL) within the Technological Pedagogical and Content Knowledge (TPACK) framework to enhance preservice teacher education. The objective is to equip educators with the skills and knowledge necessary to create inclusive learning environments that support diverse learners, particularly students with disabilities. A systematic literature review (SLR) was conducted using the PRISMA framework, with data sourced from reputable databases such as Emerald Insight, Google Scholar, and ScienceDirect. Boolean operators and keywords were employed to identify relevant studies, and five articles met the inclusion criteria after rigorous screening. The study presented an enhanced version of the Technological Pedagogical and Content Knowledge (TPACK) model that integrates assistive technology as a method of building inclusive teaching practice among prospective educators. TPACK stands for technology, pedagogy and content knowledge. This technique has significant potential to improve learning outcomes for children with disabilities and members of other underrepresented groups who get most of their education in classes that are mainstream. This research extends the TPACK paradigm by demonstrating, using specific instances, how instructional technology and assistive technology are distinct but complementary ideas. A strong focus is placed on determining the key digital competencies that preservice teachers need and the practices that boost inclusive educational practices.